The response to the metered intonation in the Arabic song (Journal of the College of Basic Education, 2023)
Since the song is the oldest and most popular musical form, it has taken a basicTo provide the student with the experience of recognizing and diagnosing maqamat in audible music. And thatPart of the experience that the student acquires, in practice, in the subject of education of hearing in the Department of ArtsFaculty of Fine Arts. In order to link the application to the theory, it is necessary to stop atThe two systems of melodic treatment in the song, in order to reveal some rules of maqam intonation.formed in it at the level of its primary structure, perhaps it provides a theoretical concept in general, since it has long beenThe melodic principle gained great independence in the song, in accordance with the development of its emotional pattern, whichbeget extended forms of structures, in the overwhelming majority of which emphasis is placed onbasic decision. And based on the position of the decision, in those structures, reference can be made to two principles.Two foundations in its formation - three stages in the first: decision - instability - decision - and two stages in the second:Don't settle - decide. And by the decision, he means the stage that enjoys a solid foundation based on the center.the denominator. As for stability, it is not specified in terms of the position and its class, because the process of tonal formationDirection is not accurate.